The structure of bovine brain myelin proteolipid and its organization in myelin. - Laursen, R A (1984)
A model, based on amino acid sequence data, is proposed for the organization of the myelin proteolipid in myelin membrane. The model has three distinctive features: three trans-membrane segments that traverse the lipid bilayer, two cis-membrane domains that enter and exit the same side of the membrane, and a highly charged segment resembling myelin basic protein on the cytoplasmic side of the membrane. It is proposed that the cis-membrane domain(s) can promote the formation and stabilization of the multilamellar myelin structure by hydrophobic interaction with the apposite bilayer across the extracellular space.